Réponses

2014-05-05T19:12:57+02:00
Bonjour
f est une fonction affine 
f(x) = ax+b
on connait 
f(2) = 11                               et               f(-3) = -26.5             soit
2a+b = 11                            et                -3a + b = -26.5
b = 11 - 2a     on remplace                      -3a + (11 - 2a) = -26.5 
                                                             -5a = -26.5 - 11 
                                                             -5a = -37.5 
                                                              a = -37.5 / -5 = 7.5 
b = 11 - 2(7.5) 
b = - 4
la fonction sera f(x) = 7.5x - 4